Utilization of a mental health collaborative care model among patients who require interpreter services. Issue 1 (December 2016) - Njeru, Jane; DeJesus, Ramona; St. Sauver, Jennifer; Rutten, Lila; Jacobson, Debra; Wilson, Patrick; Wieland, Mark
Abstract Background Immigrants and refugees to the United States have a higher prevalence of depression compared to the general population and are less likely to receive adequate mental health services and treatment. Those with limited English proficiency (LEP) are at an even higher risk of inadequate mental health care. Collaborative care management (CCM) models for depression are effective in achieving treatment goals among a wide range of patient populations, including patients with LEP. The purpose of this study was to assess the utilization of a statewide initiative that uses CCM for depression management, among patients with LEP in a large primary care practice. Methods This was a retrospective cohort study of patients with depression in a large primary care practice in Minnesota. Patients who met criteria for enrollment into the CCM [with a provider-generated diagnosis of depression or dysthymia in the electronic medical records, and a Patient Health Questionnaire-9 (PHQ-9) score ≥10]. Patient-identified need for interpreter services was used as a proxy for LEP. Rates of enrollment into the DIAMOND (Depression Improvement Across Minnesota, Offering A New Direction) program, a statewide initiative that uses CCM for depression management were measured. These rates were compared between eligible patients who require interpreter services versus patients who do not. Results Of the 7561 patients who met criteria for enrollment into the DIAMOND program during the study interval, 3511 were enrolled. Only 18.2 % of the eligible patients with LEP were enrolled into DIAMOND compared with the 47.2 % of the eligible English proficient patients. This finding persisted after adjustment for differences in age, gender and depression severity scores (adjusted OR [95 % confidence interval] = 0.43 [0.23, 0.81]). Conclusions Within primary care practices, tailored interventions are needed, including those that address cultural competence and language navigation, to improve the utilization of this effective model among patients with LEP.